The Construction of the Indonesian Government's Repressive Counter-Terrorism Policy - Ardli Johan Kusuma; Tulus Warsito; Surwandono Surwandono; Ali Muhammad; Mega Hidayati; Muhlis Madani (Department of Government Studies Universitas Muhammadiyah Makassar, 2019)
The Indonesian government has made a counter-terrorism legal instrument starting in 2001. And the making of counter-terrorism policies in Indonesia was carried out after the 9/11 event. Even though the phenomenon of terrorism that occurred in Indonesia existed before 2001. Even since Indonesia became an independent state, there have been many events that can be classified into the phenomenon of terrorism. But the Indonesian government responded by making legal instruments after 2001. In overcoming terrorism, the Indonesian government prefers a repressive approach. Detachment 88 as a special anti-terrorist force, allegedly has committed many human rights violations. Even in the last 10 years, at least 120 suspected terrorists were killed in the arrest process and 40 people were victims of wrongful arrests. In addition, more than 80% of them were subjected to torture. However, the repressive approach has not been able to reduce the number of terrorist attacks in Indonesia. Therefore, this research seeks to find what factors that influencing the Indonesian government to make repressive counter-terrorism policies in Indonesia. The findings revealed the existence of several factors including the persuasion of the international community, the influence of international norms, and the perception of the Indonesian government in understanding the threat of terrorism which is influenced by past experience.